Dietary folate intake and serum klotho levels in adults aged 40–79 years: a cross-sectional study from the national health and nutrition examination survey 2007–2016 - Liu, Yang; Zhou, Chunhuan; Shen, Rongjun; Wang, Anxian; Zhang, Tingting; Cao, Zhengyuan (Frontiers in Nutrition, 2024)
Abstract Objective: This study aims to explore the relationship between dietary folate intake and serum Klotho levels in adults from aged 40 to 79 years in the United States, seeking to elucidate the intricacies of their interaction. Methods: Analyzing data from the National Health and Nutrition Examination Survey (NHANES) spanning 2007 to 2016. The survey research determined folate intake through a 24-hour dietary recall and nutrient density modeling, and assessed Klotho levels using enzyme-linked immunosorbent assay (ELISA). The relationship between folate intake and Klotho levels was evaluated using weighted linear regression. Subsequently, a restricted cubic spline (RCS) model was employed to further investigate the nonlinear dose-response relationship between the two. Results: The study encompassed 10,278 participants, with an average age of 57.64 years, revealing a noteworthy positive correlation between dietary folate and serum Klotho levels. The regression coefficient stood at 0.11 (95% confidence interval: 0.05, 0.18) post-adjustment for various covariates. When dietary folate intake was categorized into quartiles, the second, third, and fourth quartiles exhibited statistically significant differences compared to the lowest quartile. This indicates that higher folate intake correlates with increased serum Klotho levels. These findings underscore the potential benefits of elevating folate intake to enhance serum Klotho levels.Stratified analysis indicated that this association was more pronounced among males aged 60 years or older and individuals with hypertension. Conclusion: The findings suggest a significant correlation between increased dietary folate intake and elevated serum Klotho levels in adults aged 40-79 years. hinting at the potential nutritional influences on the aging process and associated health conditions. This calls for further exploration into the mechanisms and broader implications of this association.